2018
DOI: 10.17135/jdhs.2018.18.5.271
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Turnover Intention of Dental Hygienists: Emotional Labor, Job Satisfaction, and Social Support

Abstract: This study aims to contribute to managing the human resource of dental hygienists and qualitatively enhancing dental medical services by examining factors that affect their turnover intention. Therefore, it attempted to examine their degrees of emotional labor, job satisfaction, and social support and the effects of each variable on turnover intention. This study administered self-reporting questionnaires to dental hygienists working in dental hospitals, dental clinics, and general or university hospitals in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The social support rating scale is used to carry out the questionnaire survey, which included three dimensions: subjective support, objective support, and utilization of support. Items 1, 3, 4, and 5 belong to subjective support; items 2, 6, and 7 belong to objective support; and items 8, 9, and 10 belong to the utilization of support [ 10 ].…”
Section: Nursing Staff Information and Investigated Methodsmentioning
confidence: 99%
“…The social support rating scale is used to carry out the questionnaire survey, which included three dimensions: subjective support, objective support, and utilization of support. Items 1, 3, 4, and 5 belong to subjective support; items 2, 6, and 7 belong to objective support; and items 8, 9, and 10 belong to the utilization of support [ 10 ].…”
Section: Nursing Staff Information and Investigated Methodsmentioning
confidence: 99%
“…Domestically and globally, dental hygienists wish to improve their working environment. In South Korea, Noh et al [25] concluded that working conditions are factors that are strongly related to job satisfactions and employee turnover rate. Reduction of working hours was an important factor for keeping employees from leaving.…”
Section: Discussionmentioning
confidence: 99%
“…This balance allows one to control and condition one's own life and to be satisfied with it 9) . A work-family balance can help to improve the quality of dental personnel management and dental care services at the workplace level 10) . At a national level, establishing a work-family balance plays an important role in becoming a competitive country 5) .…”
Section: Introductionmentioning
confidence: 99%